Wiejska okolica Łodzi czasów Wielkiej Wojny w publicystyce Theodora Abla i Heinricha Zimmermanna - Stawiszyńska, Aneta (Zeszyty Wiejskie, 2013)
Theodor Abel and Heinrich Zimmermann were most popular journalists publishing in Lodz during the First World War period. Both of them touched upon the topic of villages neighboring Lodz quite frequently. In both cases, their texts presented reflections concerning changes taking place in lives of citizens of Lodz’s neighboring areas, which could be observed after the war’s outbreak. Both publicists presented this topic in manners that were truly characteristic for them. Works of both journalists were published in the German „Neue Lodzer Zeitung” daily newspaper, which – in contrast to other German magazines published in Lodz at that time – presented pro-Polish attitude.